The Implementation of Combined Roughness and Reflected Model (CRRM) in Tsunami Run-up Simulation through Coastal Vegetation - Benazir Benazir; Radianta Triatmadja; Adam Pamudji Rahardjo; Nur Yuwono (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Hydraulics resistance is commonly used to simulate or replace drag and inertia forces due to vegetation when modeling tsunami run-up. A new numerical method was proposed which was named Combined Roughness and Reflected Model (CRRM). This method accommodates the reflection process of tsunami flow by tree surfaces. A series of experimental work was performed in laboratory to verify the numerical results. The physical process of laboratory work was discussed to explain the interaction between tsunami and vegetation models. The relation of some notable parameters was reviewed for both models. The physical model verified that the deviations between the physical and the numerical model were below 20%. With such numerical method, more challenging forest layout such as zigzag arrangement can be studied more accurately. It is concluded that the zigzag arrangement of trees layout and higher density of trees were capable of reducing tsunami run-up on land significantly.